(3CMOgeG aj LhGH CjgeGs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3HSe Gddg hGdMeO ddg (B... (3hHYO aEfj cfJ aj HYV GdbQi ef JhGHY HZOGO SfI (B1333(3g` aj Pdc GdYGe GdeXde hJdc GdSfI GdShOGA GdJj UHJ ajgG GdHdGAs
(3BNQgG (B:s
(3BNQgG(B: (3hdh SCdfG GdeSjMjjf hbdfG dge He YQaJe fHhI EHQGgje hehSi hZjQgeG? aEf CLGHhG(B: (3EfG YQafGgG hGdBjGJ jbGd dge Cf BjGJ eMeO CYXe hCOd hgj CbQH YgkOG (B... (3hfSCdg GdahR HGdfLGI jhe GdeYGO Efg CQMe GdQGMejf hSHMGf QH GdYRI YeG jUahfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 58s
(3GdPQjYI, L (B1: 190s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds